Análisis de la colorimetría en el lenguaje audiovisual de los programas informativos de Ecuavisa - Loayza Castillo, Estefania Isabel (2021)
The present case study in which its general objective is to analyze the colorimetry in the audiovisual language of the Ecuavisa informative programs, in which we will know in a technical way how a certain type of color is chosen for the expression of a visual harmony in a study recording or Set of a program. Observing and paying attention to it in an analytical way has elements that make up a newscast as such helps us to determine certain details to which we are not paying attention. The colorimetry compositions in the audiovisual language of the informative programs allow to give a deeper explanation of the elements that compose it, color is the main one with the help of lighting these two compositions visually allow and help a set to have a harmony perfectly balanced visual to the human eye. Within the analytical interpretations we must bear in mind that the viewers are not experts on the subject of colorimetry and that is why within the case study it will be the professionals on the subject to give us the respective analysis of this case study. It is important to know that if there are people who are dedicated to handling all these elements from a more technical part in order to have a better understanding of it.